Recent advances in oocyte and ovarian tissue cryopreservation and transplantation - Rodriguez-Wallberg, Kenny A. (2012)
Options for preserving fertility in women include well-established methods such as fertility-sparing surgery, shielding to reduce radiation damage to reproductive organs, and emergency in-vitro fertilisation after controlled ovarian stimulation, with the aim of freezing embryos. The practice of transfering frozen or thawed embryos has been in place for over 25 years, and today is a routine clinical treatment in fertility clinics. Oocytes may also be frozen unfertilised for later thawing and fertilisation by intracytoplasmic sperm injection in vitro. In recent years, oocyte cryopreservation methods have further developed, reaching promising standards. More than 1000 children are born worldwide after fertilisation of frozen and thawed oocytes. Nevertheless, this technique is still considered experimental. In this chapter, we focus on options for fertility preservation still in development that can be offered to women. These include freezing of oocytes and ovarian cortex and the transplantation of ovarian tissue.